Stakeholders of the coffee value chain, addressing households´ food insecurity and resilience to climate variation - Rodríguez Camayo, Fernando; Lundy, Mark M.; Borgemeister, Christian; Beuchelt, Tina (2023)
The survey was a randomized household survey with a 90% confidence level and a 5% precision, stratified per elevation. The sampling included five cooperatives and 348 farm households (from a universe of 716 farming households), collecting data on coffee farmers’ livelihoods, poverty, food insecurity, and income distribution. The survey had conducted in the Ocotepeque and Copan states of Honduras between September and October 2019. The survey had supported by a technical assistant from each cooperative, who coordinated the appointments with farming households.